A configurational approach to the dynamics of firm level knowledge - Ambrosini, Veronique; Collier, Nardine; Jenkins, Mark (Emerald, 2009)
Whilst there has been exponential growth in the work on the nature of organisational knowledge, relatively little progress has been made in terms of understanding the way in which knowledge specifically impacts on the firm. The aim of this paper is to further this understanding by developing a series of configurations representing some of the potential ways that knowledge is composed in organisations, with those components being tacit, explicit, architectural, component, individual and collective knowledge.
Keywords: knowledge; configuration; competitive advantage